High prevalence of severe coronary artery disease in elderly patients with non-operable chronic thromboembolic pulmonary hypertension referred for balloon pulmonary angioplasty - Roik, Marek; Wretowski, Dominik; Kostrubiec, Maciej; Dzikowska-Diduch, Olga; Łabyk, Andrzej; Irzyk, Katarzyna; Lichodziejewska, Barbara; Wyzgał, Anna; Jankowski, Krzysztof; Pruszczyk, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : Balloon pulmonary angioplasty (BPA) is a new emerging catheter-based alternative treatment option for patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH). Aim : To show that all elderly CTEPH patients referred for BPA are at higher risk of obstructive coronary artery disease and that, in daily practice, they should undergo invasive coronary angiography. Material and methods : Eleven patients at the age of at least 65 years (6 males, 5 females, 77.2 ±5.9 years) with confirmed non-operable type II or type III CTEPH, considered for BPA, underwent elective coronary angiography. Severe obstructive coronary artery disease (CAD) was diagnosed when stenosis of left main coronary artery ≥ 50% or stenosis of ≥ 70% of epicardial arteries was angiographically confirmed. We also screened for CAD consecutive age- and sex-matched 114 PE survivors (52 males, 62 females, 74.8 ±7.2 years) with excluded CTEPH. Results : Severe CAD was more frequent in elderly patients with non-operable type II or type III CTEPH candidates for BPA than in elderly acute PE survivors with excluded CTEPH (54.5% vs. 16.7%, p < 0.01), and therefore elderly CTEPH patients referred for BPA were at higher risk of CAD (OR = 5.9, 95% CI: 1.64–21.46, p = 0.007) when compared to elderly survivors after acute PE with excluded CTEPH. Conclusions : All elderly CTEPH patients referred for BPA are at higher risk of severe CAD and should routinely undergo invasive coronary angiography before BPA.